(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Objective: The sub bandage pressure results from a complex interaction between the bandage types, applied tension, number of layers and surface hardness. In this paper, three parameters i.e. hardness of the limb, stretch (%) and number of bandage layers are changed at three levels and their individual and interactive effect on the sub bandage pressure for different types of high compression bandages is studied. Method: The study has been conducted on two types of high compression bandages (woven and knitted) using the Box-Behnken Design. The data obtained for sub bandage pressure of bandage samples on three plastic tubes with layer of foam of varying hardness is used to carry out response surface regression analysis and analysis of variance to find the contribution of each parameter on the sub bandage pressure for high compression bandages. Results: The effect of hardness is significant specifically in the case of woven bandages with some interactive effects with stretch (%) in knitted bandages. The sub bandage pressure increases with the increase in stretch% for all the samples but larger pressure differences were observed for increase in stretch % for limbs with higher hardness. The sub bandage pressure also increases with the number of bandage layers but a linear relationship was not observed between sub bandage pressure and the number of layers at low stretch %. The regression equations for various responses agree well with the experimental data as indicated by higher values of coefficient of determination. Conclusion: The number of layers and the stretch % contribute substantially towards the sub bandage pressure for both woven and knitted bandages. The contribution of hardness of the limb is found to be insignificant for knitted bandage sample which has the tightest structure and high initial modulus. The regression equations generated for various responses can be used to predict the sub bandage pressure of bandages during application of high stretch bandages.